Neo-liberal impacts on administrative reform: Public-private partnerships in health policy - Bjorkman, James Warner (2013)
This article sketches the emergence of neo-liberal approaches in world health policy, reviews the logic of New Public Management in the health care sector, examiners reforms for the delivery of health services through public-private partnerships, and suggests strategies for public policy that take capacity into account. - Reproduced.
Keywords: Public private partnerships; Health services; Administrative reform